Testing accelerated experience-based co-design: a qualitative study of using a national archive of patient experience narrative interviews to promote rapid patient-centred service improvement - Louise Locock; Glenn Robert; Annette Boaz; Sonia Vougioukalou; Caroline Shuldham; Jonathan Fielden; Sue Ziebland; Melanie Gager; Ruth Tollyfield; John Pearcey (National Institute for Health Research, 2014)
Background: Measuring, understanding and improving patients' experiences is of central importance to health care systems, but there is debate about the best methods for gathering and understanding patient experiences and how to then use them to improve care. Experience-based co-design (EBCD) has been evaluated as a successful approach to quality improvement in health care, drawing on video narrative interviews with local patients and involving them as equal partners in co-designing quality improvements. However, the time and cost involved have been reported as a barrier to adoption. The Health Experiences Research Group at the University of Oxford collects and analyses video and audio-recorded interviews with people about their experiences of illness. It now has a national archive of around 3000 interviews, covering around 75 different conditions or topics. Selected extracts from these interviews are disseminated for a lay audience on www.healthtalkonline.org. In this study, we set out to investigate whether or not this archive of interviews could replace the need for discovery interviews with local patients. Objectives: To use a national video and audio archive of patient experience narratives to develop, test and evaluate a rapid patient-centred service improvement approach ('accelerated experience-based co-design' or AEBCD). By using national rather than local patient interviews, we aimed to halve the overall cycle from 12 to 6 months, allowing for EBCD to be conducted in two clinical pathways rather than one. We observed how this affected the process and outcomes of the intervention. Design: The intervention was an adapted form of EBCD, a participatory action research approach in which patients and staff work together to identify and implement quality improvements. The intervention retained all six components of EBCD, but used national trigger films, shortened the time frame and employed local service improvement facilitators. An ethnographic process evaluation was conducted, including observations, interviews, questionnaires, cost and documentary analysis including previous EBCD evaluation reports. Setting: Intensive care and lung cancer services in two English NHS hospital trusts (Royal Berkshire and Royal Brompton and Harefield). Participants: Ninety-six clinical staff (primarily nursing and medical) and 63 patients and family members. Intervention: For this accelerated intervention, the trigger film was derived from pre-existing national patient experience interviews. Local facilitators conducted staff discovery interviews. Thereafter, the process followed the usual EBCD pattern: the film was shown to local patients in a workshop meeting, and staff had a separate meeting to discuss the results of their feedback. Staff and patients then came together in a further workshop to view the film, agree priorities for improvement and set up co-design working groups to take these priorities forward. Results: The accelerated approach proved readily acceptable to staff and patients; using films of national rather than local narratives did not adversely affect local NHS staff engagement, and may in some cases have made the process less threatening or challenging. Local patients felt that the national films generally reflected important themes, although a minority felt that they were more negative than their own personal experience. However, they served their purpose as a 'trigger' to discussion, and the resulting 48 co-design activities across the four pathways were similar in nature to those in EBCD but achieved at reduced cost. AEBCD was nearly half the cost of EBCD. However, where a trigger film already exists, pathways can be implemented for as little as 40% of the cost of traditional EBCD. It was not necessary to do additional work locally to supplement the national interviews. The intervention carried a 'cost' in terms of heavy workload and intensive activity for the local facilitators, but also brought benefits in terms of staff development/capacity-building. Furthermore, as in previous EBCDs, the approach was subsequently adopted in other clinical pathways in the trusts. Conclusions: Accelerated experience-based co-design delivered an accelerated version of EBCD, generating a comparable set of improvement activities. The national film acted as an effective trigger to the co-design process. Based on the results of the evaluation, AEBCD offers a rigorous and effective patient-centred quality improvement approach. We aim to develop further trigger films from the archived material as resources permit, and to investigate different ways of conducting the analysis (e.g. involving patients in doing the analysis). Funding: The National Institute for Health Research Health Services and Delivery Research programme.